The death penalty as torture: from the Dark Ages to abolition - Bessler, John D. (Carolina Academic Press, 2017)
The dark ages -- The enlightenment -- The abolition movement -- The machinery of death -- The U.S. Supreme Court -- The Law and its evolution -- Lawful vs. unlawful sanctions -- The death pealty as torture --- A Jus Cogens norm